Thought Field Therapy Compared to Cognitive Behavioral Therapy and Wait-List for Agoraphobia: A Randomized, Controlled Study with a 12-Month Follow-up - Audun C. Irgens; Asle Hoffart; Asle Hoffart; Tor E. Nysæter; Vegard Ø. Haaland; Vegard Ø. Haaland; Finn-Magnus Borge; Are H. Pripp; Egil W. Martinsen; Toril Dammen (Frontiers in Psychology, 2017)
Background: Thought field therapy (TFT) is used for many psychiatric conditions, but its efficacy has not been sufficiently documented. Hence, there is a need for studies comparing TFT to well-established treatments. This study compares the efficacy of TFT and cognitive behavioral therapy (CBT) for patients with agoraphobia.Methods: Seventy-two patients were randomized to CBT (N = 24), TFT (N = 24) or a wait-list condition (WLC) (N = 24) after a diagnostic procedure including the MINI PLUS that was performed before treatment or WLC. Following a 3 months waiting period, the WL patients were randomized to CBT (n = 12) or TFT (n = 12), and all patients were reassessed after treatment or waiting period and at 12 months follow-up. At first we compared the three groups CBT, TFT, and WL. After the post WL randomization, we compared CBT (N = 12 + 24 = 36) to TFT (N = 12 + 24 = 36), applying the pre-treatment scores as baseline for all patients. The primary outcome measure was a symptom score from the Anxiety Disorders Interview Scale that was performed by an interviewer blinded to the treatment condition. For statistical comparisons, we used the independent sample’s t-test, the Fisher’s exact test and the ANOVA and ANCOVA tests.Results: Both CBT and TFT showed better results than the WLC (p < 0.001) at post-treatment. Post-treatment and at the 12-month follow-up, there were not significant differences between CBT and TFT (p = 0.33 and p = 0.90, respectively).Conclusion: This paper reports the first study comparing TFT to CBT for any disorder. The study indicated that TFT may be an efficient treatment for patients with agoraphobia.Trial Registration:https://clinicaltrials.gov/, identifier NCT00932919.